2011
DOI: 10.1001/archgenpsychiatry.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Cerebral Serotonin Transporter and Serotonin2A Receptor Binding in 3,4-Methylenedioxymethamphetamine (MDMA or “Ecstasy”) and Hallucinogen Users

Abstract: We found evidence that MDMA but not hallucinogen use is associated with changes in the cerebral presynaptic serotonergic transmitter system. Because hallucinogenic drugs primarily have serotonin(2A) receptor agonistic actions, we conclude that the negative association between MDMA use and cerebral SERT binding is mediated through a direct presynaptic MDMA effect rather than by the serotonin(2A) agonistic effects of MDMA. Our cross-sectional data suggest that subcortical, but not cortical, recovery of SERT bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 83 publications
5
73
1
Order By: Relevance
“…More recently, PET studies have reported 5-HT 2A receptor upregulation after chronic MDMA use over broad areas of the cerebral cortex, including: occipital parietal, frontal and frontoparietal regions (Di Iorio et al, 2012) and the dorsolateral prefrontal cortex (DLPFC) and parietal cortex (Urban et al, 2012), which is thought to be due to a loss or reduction in presynaptic signalling. Furthermore, McCann et al (2008), Kish et al (2010) and Erritzoe et al (2011) found reduced SERT binding in abstinent users after recreational use, which is interpreted as compensatory down-regulation. A complicating factor emerges in research in recreational ecstasy users as the majority of individuals who report recreational use of ecstasy use a range of other drugs in addition to ecstasy (Fox et al, 2001;Parrott et al, 2008;Roberts et al, 2013Roberts et al, , 2014 however, in most cases, they report that ecstasy is their "drug of choice".…”
Section: Introductionmentioning
confidence: 99%
“…More recently, PET studies have reported 5-HT 2A receptor upregulation after chronic MDMA use over broad areas of the cerebral cortex, including: occipital parietal, frontal and frontoparietal regions (Di Iorio et al, 2012) and the dorsolateral prefrontal cortex (DLPFC) and parietal cortex (Urban et al, 2012), which is thought to be due to a loss or reduction in presynaptic signalling. Furthermore, McCann et al (2008), Kish et al (2010) and Erritzoe et al (2011) found reduced SERT binding in abstinent users after recreational use, which is interpreted as compensatory down-regulation. A complicating factor emerges in research in recreational ecstasy users as the majority of individuals who report recreational use of ecstasy use a range of other drugs in addition to ecstasy (Fox et al, 2001;Parrott et al, 2008;Roberts et al, 2013Roberts et al, , 2014 however, in most cases, they report that ecstasy is their "drug of choice".…”
Section: Introductionmentioning
confidence: 99%
“…Regression analysis was used to investigate possible correlations between reaction times (RT) and log 2 to the lifetime intake of ecstasy tablets or log 2 to the number of days since the last use of ecstasy. Due to our previous findings that the effects of cumulative ecstasy lifetime intake and time since last use of ecstasy on SERT binding follow a log 2 at UNIV CALIFORNIA SAN DIEGO on October 14, 2016 jop.sagepub.com Downloaded from distribution, we expected a log 2 -linear relationship between RT and lifetime intake and time since last use (for calculation of number of ecstasy tablets, please see Erritzoe et al, 2011). Analysis and results that include lifetime intake and/or number of days since last use of ecstasy (and the same is the case for amphetamine) will in this manuscript refer to "log 2 to" the number of accumulated lifetime doses/time since last use, but in order to improve readability, in the Results and Discussion sections, we have left out "log 2 to" from the text.…”
Section: Participantsmentioning
confidence: 99%
“…The degree of serotonin depletion as reflected by cerebral SERT binding was assessed with PET and the selective SERT radioligand, 11C-DASB, as described in more detail by Erritzoe et al (2011). In short, PET data were acquired on a GE-Advance scanner (GE, Milwaukee, WI) as a dynamic 90-minute emission recording after intravenous injection of the radiotracer, 11C-DASB.…”
Section: Mdma Use and Sert Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, serotonergic (Erritzoe et al, 2011;Reneman et al, 2002) and cognitive (Adamaszek et al, 2010;Nulsen et al, 2010;Parrott et al, 1998;Quednow et al, 2006) deficits have been reported in human chronic MDMA users, which could be due to neurotoxicity or to drug-induced long-lasting regulatory changes (Biezonski and Meyer., 2011).…”
Section: Introductionmentioning
confidence: 99%